2007
DOI: 10.1074/jbc.m610580200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lipolytic Protein Trafficking and Interactions in Adipocytes

Abstract: A central function of adipocytes is the storage and mobilization of energy in the form of triglyceride. A considerable amount is known about the enzymatic basis for lipogenesis and lipolysis; however, our understanding of how these processes are organized and regulated within cells is incomplete. Until recently, cellular triglyceride was considered to be stored in droplets lacking biological structure or organization. Growing evidence, however, suggests that lipid droplets are specialized, heterogeneous organe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
293
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(309 citation statements)
references
References 33 publications
12
293
2
2
Order By: Relevance
“…The localized metabolic subdomain is consistent with a small cytosolic volume due to large lipid droplet in adipocyte (Moore et al, 2005;Denton et al, 1966). Furthermore, the volume fraction of this metabolic subdomain estimated by the model corresponds to the volume fraction of intracellular water space (1~4% of total tissue volume) measured from in vitro studies of adipose fat pad (Denton et al, 1966;Crofford and Renold, 1965) Recent in vitro studies of adipocyte lipid mobilization showed that major lipolytic enzymes and proteins are co-localized in a subcellular domain during beta-adrenergic stimulation (Granneman et al, 2007;Moore et al, 2005;Clifford et al, 2000). The localization of enzyme complexes reduces the transit time of metabolites which allows faster cellular dynamics (Welch and Easterby, 1994).…”
Section: Intracellular Compartmentationsupporting
confidence: 69%
“…The localized metabolic subdomain is consistent with a small cytosolic volume due to large lipid droplet in adipocyte (Moore et al, 2005;Denton et al, 1966). Furthermore, the volume fraction of this metabolic subdomain estimated by the model corresponds to the volume fraction of intracellular water space (1~4% of total tissue volume) measured from in vitro studies of adipose fat pad (Denton et al, 1966;Crofford and Renold, 1965) Recent in vitro studies of adipocyte lipid mobilization showed that major lipolytic enzymes and proteins are co-localized in a subcellular domain during beta-adrenergic stimulation (Granneman et al, 2007;Moore et al, 2005;Clifford et al, 2000). The localization of enzyme complexes reduces the transit time of metabolites which allows faster cellular dynamics (Welch and Easterby, 1994).…”
Section: Intracellular Compartmentationsupporting
confidence: 69%
“…A large number of hormonal signaling pathways and lipid droplet-associated protein factors have been demonstrated to regulate substrate access and the activity of lipase, and thereby to govern the lipolysis of white adipose tissue [31,32] . Our data showed that the phosphorylation of HSL and expression of CGI-58 were increased in the tissue of the RRM rats.…”
Section: Discussionmentioning
confidence: 99%
“…To initiate lipolysis, catecholamines bind to β-adrenergic receptors to activate adenylyl cyclase, which results in increased intracellular concentrations of cyclic AMP and, thus, activated protein kinase A (PKA). PKA phosphorylates HSL and perilipin, with subsequent translocation of HSL from the cytosol to the lipid droplets [13], leading to the hydrolysis of triacylglycerols. Catecholamine release is increased when there is an increased energy demand (e.g.…”
Section: Biological Differences Between Visceral and Subcutaneous Adimentioning
confidence: 99%